Going cyber: the dynamics of cyber proliferation and international security - Smeets, M (2017)
For over a decade, we have heard alarming statements about the spread of cyber weapons from senior policymakers and experts. Yet, the dynamics of cyber proliferation are still understudied and under- theorized. This study offers a theoretical and empirical account of what causes the spread and restraint of cyber weapons and argues that the world is not at the brink of mass cyber proliferation. Whilst almost forty states are exploring and pursuing the development of cyber weapons, I indicate that only few have so far acquired a meaningful capability. This is due both to supply and demand factors. On the supply-side, most states have a latent capacity to develop relatively simple offensive cyber capabilities, but are unable to develop sophisticated cyber weapons. Moreover, the incentives for knowledge transfer and thus exporting offensive cyber capabilities between states are weak. On the demand-side, I show that national security considerations do not provide the best explanation of variance. Instead, domestic politics and prestige considerations are paramount. Moreover, and unlike nuclear proliferation, I argue that it is not the possession of cyber weapons but the intention of possession signalled through visible initiatives which matters. Ultimately, I note that cyber weapons can have strategic value – but only under certain conditions.